Validating the effects of organizational internal factors and technology orientation on environmental sustainability performance of Malaysian Construction firms - Ajibike, W. A.; Adeleke, A. Q.; Fazeeda, Mohamad; M.N.M., Nawi; Bamgbaded, J. A.; S. R. M., Riazi; M.F., Ahmad (GITO Verlag, P, 2021)
The essence of emphasizing the value of environmental sustainability for construction companies is to reduce the environmental footprint of construction operations or projects and make construction activities more environmentally friendly and economically competitive. Due to the harmful consequences of construction practices such as various aspects of environmental degradation, resource destruction, and loss of biodiversity on a global scale, this critical deliberation has prompted different research interests among construction companies. Using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach, this study validates the environmental sustainability performance (ESP) as a construct within Peninsular Malaysia from the perspective of 186 construction companies. An online cross-sectional survey was performed where a well-structured questionnaire obtained data from G7 construction firms. Findings from this study revealed that internal organizational factors (managerial attitudes, social responsibility, and company culture) and technology orientation have significant effects on the environmental sustainability performance (ESP) of Malaysian construction firms.